Vertical Garden Identification and Plant Species Diversity of Urban Green Space in Banda Aceh City, Indonesia - Yahya, Rizka Ora Aurora; Arifin, Hadi Susilo; Perdinan, Perdinan (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Vertical gardens (VG) applies plant growth to various wall media and/or other vertical surfaces. In Banda Aceh City, these urban greening innovations are beginning to create trends as they boost building esthetics. The objectives of this research were to identify the various types of vertical gardens and to analyze people's preferences, including the design and variety of plants used in these types of vertical gardens, between January and September 2022 in nine sub-districts of Banda Aceh City, Aceh Province, Indonesia. The research method involved an exploratory survey of the entire city where VG was applied in various public spaces, private and public organizations, residential housing, hotels, mosques, various business culinary, and cafeterias. Data on garden preferences were collected and analyzed using descriptive methodology, and the Shannon-Wiener Formula was used to examine the species diversity index. From a total of 166 documented gardens and 150 sample locations where vertical gardens were observed, 66 plant species were discovered. Vertical gardens are most frequently used in residential housing. Ficus pumilla (dollar creeper) is the plantmost frequently used by the community, and green facades are the most common style of vertical garden design applications. In the nine sub-districts, the highest diversity index was found in the Syiah Kuala Sub-district with H' 2.9, and the lowest diversity index was found in the Kuta Raja subdistrict with H’ 1.2. Based on plant function, there were 43 species of ornamental plants, 13 species of flowering plants, 7 species of fruitful plants, and 3 species of herbs.